Whole-Body 18FDG-PET in an Arthritis Paraneoplastic Syndrome Revealed an Underlying Hematological Neoplasm. (30th May 2013) - Cammilleri, Serge; Guzian, Marie Caroline; Mattei, Jean-Pierre; Mundler, Olivier; Guis, Sandrine
Abstract : We showed the first image of 18 FDG-PET, which leads to a diagnosis of lymphoma in an atypical polyarthritis. About 4% of patients with lymphoma or leukemia suffered from rheumatologic paraneoplastic symptoms like arthralgia and about 10% of the patients with rheumatologic or neurologic clinical symptoms develop a solid cancer or hematological neoplasm. 18 FDG-PET is an interesting exam to identify an underlying malignancy when a paraneoplastic syndrome is suspected; it can detect the primitive lesion and/or the metastasis lesions. The use of the 18 FDG-PET can help to detect earlier hematological neoplasm in cases of paraneoplastic syndrome without a determined cause and to treat more rapidly and specifically the patient.